SUPERVISION FOR ADVOCACY: SUPPORTING SELF-CARE - FARKAS, KATHLEEN J.; ROMANIUK, JAROSLAW R. (Society Register, 2021)
The objective is to examine the intersection of advocacy for social change, the individual’s emotional costs of advocacy, and the use of trauma informed care in supervisory practice to encourage and support advocates and their work. Supervision models exist, but none address the needs of advocates who might become targets for scorn and persecution. The literature on trauma informed care provides a direction to improve the support and supervision of advocates, especially those who use their personal experiences as examples in their work. We reviewed data bases and relevant literature regarding supervision and the principles of trauma informed care. Periodical literature was reviewed for examples of those affected personally and professionally by their advocacy efforts. Review of the literature revealed little new knowledge on supervision but provided a base to apply the principles of trauma informed care to support and encourage advocacy for social change. This paper suggests the use of trauma informed care in supervisory relationships and advocacy work. This is an original approach to encourage and uphold advocates in difficult times.